Effect of niobia on the crystal structure and dielectric characteristics of Pb(Zr0.45Ti0.55)O-3 prepared from polymeric precursor - Paiva-Santos, C. O.; Oliveira, C. F.; Las, W. C.; Zaghete, M. A.; Varela, José Arana [UNESP]; Cilense, M. (Elsevier B.V., 2000)
The influence of niobia addition on the phase formation and dielectric properties of Pb(Zr0.45Ti0.55)O-3 powder prepared from polymeric precursor was analyzed. The weight fraction and unit-cell volume of the tetragonal phase decreased, and the mass fraction of the rhombohedral phase increased, with increasing niobia concentration. The rhombohedral unit-cell volume increased up to 5 mol% of added Nb and then decreased. Small amounts of pyrochlore and tetragonal zirconia phases were observed in PZT powder with more than 10 mol% Nb. These results were interpreted as an indication that the Nb ion was substituted for the zirconium ion in the tetragonal phase. For sintered PZT samples at 1100 degrees C, no free-zirconia phase was observed. The dielectric constant increased with the niobia addition up to 5 mol% and decreased for higher concentrations. The Curie temperature decreased with niobia addition up to 10 mol% before the formation of pyrochlore phase. (C) 2000 Elsevier B.V. Ltd. All rights reserved.
Keywords: ceramics; chemical synthesis; X-ray diffraction; crystal structure; dielectric properties